Investigation of an engine order noise cancellation system in a super sports car - Ferrari Cesare Lupo; Cheer Jordan; Mautone Mario (Acta Acustica, 2023)
Today’s cars must meet ever-higher acoustic standards, and so, to avoid compromising vehicle dynamics, handling performance and fuel consumption, standard passive methods alone do not provide sufficient performance. Active control solutions can provide a potential solution to this challenge, particularly at low frequency and such systems have been investigated for application to small cars, SUVs and luxury vehicles. These vehicles are generally characterised by fairly slow dynamics and limited noise emission and, therefore, this paper explores the challenging application of active noise control to a two-seat super sports car equipped with a naturally aspirated engine. This work aims to track and then control sounds characterised by extremely rapid frequency variation rates, up to peaks of over 80 Hz/s, and high sound pressure levels. A multi-channel, multi-order FxLMS based control system has been implemented, which has been modified to optimise performance for this application by including both convergence gain and leakage scheduling, to achieve effective control at the driver’s and passenger’s ears. To evaluate the performance of the controller, its performance has been simulated when applied to measurements taken under several vehicle manoeuvres, ranging from conventional constant engine speed to very fast engine run-ups. From the presented results, it is shown that the system can obtain high levels of control during the manoeuvre set, with the controller reducing the overall sound pressure level by more than 10 dB at certain frequencies when analysing a single order, and it reduces the overall loudness by around 5% in all of the analysed cases.